2012
DOI: 10.1186/1472-6939-13-21
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of informed consent in a resource-limited setting: A cross-sectional study

Abstract: BackgroundThe process of obtaining informed consent continues to be a contentious issue in clinical and public health research carried out in resource-limited settings. We sought to evaluate this process among human research participants in randomly selected active research studies approved by the School of Medicine Research and Ethics Committee at the College of Health Sciences, Makerere University.MethodsData were collected using semi-structured interviewer-administered questionnaires on clinic days after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 22 publications
1
26
1
Order By: Relevance
“…; Taiwo & Kass ; Kiguba et al . ). Most participants in countries with poorer comprehension had a low level of education.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Taiwo & Kass ; Kiguba et al . ). Most participants in countries with poorer comprehension had a low level of education.…”
Section: Resultsmentioning
confidence: 97%
“…; Kiguba et al . ) demonstrated comprehension about voluntariness towards participation (95% CI 39.0–98.5%), with perceived medical benefit cited as a main determinant (Leach et al . ; Pace et al .…”
Section: Resultsmentioning
confidence: 99%
“…Not all participants understood that their names would not be used for presentations or that study staff could not contact their family and friends without approval. Additionally, it was not well understood that they could stop taking part in the study at any time or that medical care for TB could be obtained separately from the study, similar to findings from a previous report (Kiguba et al 2012). It is important to note that a participant’s misunderstanding of the right to confidentiality would not undermine the effectiveness of this protection; however, the right to withdraw from a study is under the volitional control of the participant.…”
Section: Discussionmentioning
confidence: 72%
“…In practice, however, achieving genuine informed consent continues to be a major challenge in many settings. Indeed, several studies have consistently shown that potential participants have major problems in understanding the basic elements of a research project as outlined on the information sheet even after repeated explanations and questioning [9][10][11][12][13][14]. Others may have serious misunderstanding including the inability to distinguish between research and clinical practice [14,15], or failure to acknowledge that they are even taking part in a research [16].…”
Section: Introductionmentioning
confidence: 99%